(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article examines the relationship between institutional quality and green economic growth in Uzbekistan. Drawing upon insights from environmental governance, policy instruments, innovation and technology transfer, sustainable infrastructure, and capacity building, the article provides a comprehensive analysis of the key dimensions of Uzbekistan’s transition towards a sustainable and inclusive economy. By addressing institutional deficiencies and fostering a conducive policy environment for green investments and innovation, Uzbekistan can unlock its green growth potential, enhance resource efficiency, and mitigate environmental risks. The article offers recommendations for policymakers, businesses, and civil society actors to advance the green growth agenda and promote prosperity, equity, and environmental sustainability in Uzbekistan.